EVALUATION OF THE EFFECT OF DIFFERENT CONCENTRATIONS OF ALOE VERA ON INFLAMMATION AND REEPITHELIALIZATION IN DIABETIC ULCERS IN A RAT MODEL - Sari, Yunita; Purnawan, Iwan; Sutrisna, Eman; Kurniawan, Dhadhang Wahyu; Nasruddin, Nasruddin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to evaluate the effect of different concentrations of Aloe vera (AV) on inflammation of diabetic ulcers in a rat model. Methods: The induction of diabetes was conducted by injection of alloxan monohydrate. This study involved four groups, including 0%, 10%, 30%, and inner leaf AV (ILAV) gel groups. Necrotic tissue, wound size, inflammation, and reepithelialization were evaluated. Wound tissue was collected on days 4 and 8. Histological analysis was performed by hematoxylin and eosin staining. Differences in the intensity of inflammation were analyzed using Kruskal–Wallis test followed by Mann–Whitney U-test. Results: On day 13, wounds in gels containing AV were almost completely healed, whereas wounds in the 0% gel group (control) were still covered with necrotic tissue. On day 3, the intensity of inflammation in the 30% and ILAV groups was significantly less when compared to the 10% and control groups. On day 8, inflammation was less significant in the 10%, 30%, and ILAV groups when compared with the control group. Moreover, the intensity of inflammation in the 30% and ILAV groups was significantly less compared to the 10% group. In addition, reepithelialization was more advanced in the 10% and 30% ILAV groups compared with the control group, and reepithelialization was most advanced in the 30% and ILAV groups. Conclusion: Our study indicated that gels containing AV reduced inflammation and improved reepithelialization of diabetic ulcers in a rat model. Therefore, it is highly recommended for clinicians to use AV gels for topical treatment of diabetic ulcers.